Method of adsorbing dye in aqueous solution. - Abdullah, Luqman Chuah; Mobarekeh, Mohsen Nourouzi; Choong, Thomas Shean Yew; Idris, Azni (2010)

(untitled)
The present invention further provides a method of adsorbing dye by chemically-modified palm kernel shell comprising the steps of: providing and treating palm kernel shell; dissolving the palm kernel shell in a epoxide solution comprising N-(3-chloro-2-hydroxypropyl) trimethylammonium chloride and a base to form a quaternized or cationized palm kernel shell; neutralizing and washing the quaternized or cationized palm kernel shell; and adding the quaternized or cationized palm kernel shell in a dye solution to adsorb the dye.